North American Glyptodontines (Xenarthra, Mammalia) in the Upper Pleistocene of northern South America - Carlini, Alfredo Armando (2008)
The Glyptodontidae is one of the most conspicuous groups in the Pleistocene megafauna of the Americas. The Glyptodontinae were involved in the Great American Biotic Interchange (GABI) and their earliest records in North America are about 3.9 Ma, suggesting an earlier formation of the Panamanian landbridge. Taxonomically it is possible to recognize two Pleistocene genera of Glyptodontinae:Glyptodon (ca. 1.8 – 0.008 Ma), restricted to South America, andGlyptotherium (ca. 2.6 – 0.009 Ma), including records in both North and Central America. Here we present the first report of the genusGlyptotherium in South America, from the Late Pleistocene of several fossil localities in Falcon State, northwestern Venezuela. A comparative analysis of the material, represented by cranial and postcranial parts, including the dorsal carapace and caudal rings, suggests a close affinity withGlyptotherium cylindricum (Late Pleistocene of Central Mexico). This occurrence in the latest Pleistocene of the northernmost region of South America Supports the bidirectional faunal migration during the GABI and the repeated re-immigration from North America of South American clades, as has been reported in other members of the Cingulata (e.g., Pampatheriidae).